Utilização da tomografia computadorizada para o diagnóstico da articulação temporomandibular - SILVEIRA, Olívia dos Santos (Universidade Federal do Pará, 2018)
The computed tomography plays an important role in the diagnosis of anomalies and pathological conditions of the TMJ, providing a complete visualization of joint region, providing a more accurate diagnosis. For evaluation of the images is necessary to the professional the knowledge of sectional anatomy of the joint region, so he can recognize the structural changes. Therefore, it was explained and described in this study the characteristics of normal CT, morphological and pathological conditions commonly found in the region of the temporomandibular joint. The Computed tomography is an imaging exam superior than the conventional imaging exam for TMJ, because it allows an adequate and accurate three-dimensional visualization of all details of the bone, without the limitation of overlap, providing the real size and shape of the anatomical structures, morphological changes and pathological conditions.